Flexible pulses from carbon nanotubes mode-locked fiber laser - 杨玲珍 杨义 王娟芬 (Chinese physics B, 2016)
We demonstrate a flexible erbium-doped pulsed fiber laser which achieves the wavelength and pulse width tuning by adjusting an intracavity filter. The intracavity filter is flexible to achieve any of the different wavelengths and bandwidths in the tuning range. The wavelength and width of pulse can be tuned in a range of - 20 nm and from - 0.8 ps to 87 ps, respectively. The flexible pulsed fiber laser can be accurately controlled, which is insensitive to environmental disturbance.